Effects of drug price reduction and prescribing restrictions on expenditures and utilisation of antihypertensive drugs in Korea. Issue 7 (15th July 2015) - Yoo, Ki-Bong; Lee, Sang Gyu; Park, Sohee; Kim, Tae Hyun; Ahn, Jeonghoon; Cho, Mee-Hyun; Park, Eun-Cheol
Abstract : Objectives: To evaluate the quantitative effects of the drug price reduction on pharmaceutical expenditures and the new guidelines to restrict prescribing on drug utilisation for antihypertensive drugs. Design: We used an interrupted time series design with the National patient sample data of Health Insurance Review and Assessment Service in South Korea. Methods: 54 295 participants who were with primary hypertension from the National patient sample data of Health Insurance Review and Assessment Service were included. The study period was from March 2011 to December 2013. The dependent variables were antihypertensive drug costs, antihypertensive drug cost per prescribing day, daily drug utilisation, average number of drugs per month, percentage of original drugs per prescription, drug overutilisation and prohibited combinations. Segmented regression analysis was used. Results: The drug price reduction reduced expenditure (US−1.51, −10.2%), and the new guidelines reduced expenditures even more (US−2.13; −16.2%). These policies saved US4.22 (28%) of antihypertensive drug costs per patient in December 2013 compared to March 2012. Drug price reduction policy was introduced in April 2012. We established the policy effect by comparing it before (March 2012) with after(21 months later-December 2012). The effects of the guidelines decreased expenditures, daily drug utilisation and the average number of drugs per month more than did the drug price reduction. Conclusions: Both policies saved money. The guidelines were more effective over time and had fewer side effects such as increasing daily drug utilisation and number of drugs than the effects of drug price reduction.